E?ect of Dexmeditomidine on Iso?uorane Consumption in Middle Ear Surgery - Smriti Bandhu; Arunabh Mukharjee (Academia Anesthesiologica International, 2020)
Background: With the introduction of intentional hypotensive anesthesia in the surgical field to achieve a relatively bloodless surgical field along with the use of the operative microscope, it has revolutionized the middle ear surgery practice. Dexmedetomidine is a relatively new and potent ?2 agonist prototype found efficient in rendering bloodless intra-surgical field and inducing controlled hypotension during the surgeries of the middle ear. The objective is to present prospective study was aimed at evaluating with and without dexmedetomidine infusion effect on end-tidal isoflurane concentration for lowering blood pressure by 30%, awakening time and quality of bloodless surgical field during middle ear surgical procedure. Subjects and Methods:54 patients who were to undergo middle ear surgery and had ASA I and II were randomly divided into the two groups. In Group I Dexmedetomidine was used and in Group II Normal saline. Effect of Dexmedetomidine infusion on end-tidal isoflurane concentration for lowering blood pressure by 30%, awakening time, quality of bloodless surgical field during middle ear surgical procedure, heart rate was evaluated. The data collected were statistically analyzed. Results: The mean values of the heart rate were statistically non-significant between the groups when recorded at the baseline, whereas, a statistically significant difference was seen in the values for heart rate intra-operatively. The mean values for heart rates were significantly higher for the placebo group. A significant difference in Isoflurane concentration was found with dexmedetomidine requiring a percentage of 0.6 0.4 and normal saline 1.8 0.5. Less bleeding was seen with dexmedetomidine. Conclusion:  Dexmedetomidine is a potent hypotensive agent which also reduces the requirement of Isoflurane compared  to the normal saline placebo. The use of dexmedetomidine is relatively safe and provide a relatively bloodless surgical field, hence, increasing efficacy, and improving visibility at the surgical site.